Prescribing pattern of oral anti-diabetic agents in type 2 diabetes mellitus patients in a tertiary care hospital - Sharma, Taruna; Sahai, Rajit; Bala, Suman; Dhasmana, Dilip C.; Kaeley, Nidhi (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Prescription pattern studies are a tool for assessing the prescribing, dispensing and distribution of medicines. The main aim of assessing prescribing pattern is to facilitate rational use of medicines. So the main aim of the study was to assess the prescribing pattern of oral anti-diabetic agents in type 2 diabetes mellitus, to assess the rationality of the prescribed drugs and also to assess the pattern of co-morbid conditions associated with type 2 diabetes mellitus in a tertiary care hospital. Methods: This cross sectional study was conducted in the Department of Pharmacology in collaboration with Department of General Medicine. Study was conducted from 1st June 2016 to 31st Aug 2016 (3 months). A total of 100 patients were enrolled after taking written informed consent. A structured case recording form was used to record demographic details and prescription details. The rationality of prescriptions was assessed using American Diabetes Association guidelines 2015. Results: Majority of the patients were prescribed combination therapy (54%) followed by monotherapy (46%). Oral anti-diabetic agents used as monotherapy other than metformin were inappropriate. Among the patients receiving combination therapy majority were receiving a fixed dose combination which were inappropriate. Conclusions: Majority of the patients were receiving fixed dose combinations without justifiable pharmacokinetic/pharmacodynamic benefits. Such kinds of studies are required to improve rationality of prescription of drugs, decreasing morbidity and mortality of patients and decreasing the cost of treatment.